Can luxury attitudes impact sustainability? The role of desire for unique products, culture, and brand self‐congruence. Issue 11 (20th July 2021) - Eastman, Jacqueline K.; Iyer, Rajesh; Dekhili, Sihem
Abstract: This study examines the effect of value‐expressive and social‐adjustive luxury attitudes on sustainable behaviors, specifically ecologically conscious consumer behavior, and socially responsible consumer behavior. This study investigates the mediating effect of the desire for unique products on the relationship between value‐expressive and social‐adjustive attitudes and sustainable behaviors. The moderating roles of brand self‐congruence and the cultural values of collectivism and masculinity on these relationships are also explored. The results offer support for the mediating role of the desire for unique products. Furthermore, the connection between the desire for unique products and ecologically conscious consumer behavior (but not socially responsible consumer behavior) is enhanced with the moderating cultural value of collectivism and the connection between the desire for unique products and socially responsible consumer behavior (but not ecologically conscious consumer behavior) is enhanced by the moderating factor of brand self‐congruence. The findings help to explain the conflicting findings regarding luxury and sustainability.